Analysis and Cross-Coupling Elimination of Input-Series Output-Parallel (ISOP) Multi-Channel IPT System - Pan Sun; Leyu Wang; Yan Liang; Xusheng Wu; Qijun Deng (IEEE Open Journal of Power Electronics, 2024)
To meet the low-voltage and high-power demand of fast charging of electric vehicles, an ISOP multi-channel inductive power transfer (IPT) system based on LCC-S compensation network is analyzed in this paper. Firstly, the system's improvement of transmission capability is analyzed without considering the cross-coupling. After that, to clarify the cross-coupling impression, the equivalent impedance formula for the inverter output terminals of each channel is calculated. Then, combined with the harmonic characteristics of high order topology, the zero voltage switching (ZVS) condition of each channel is analyzed. Found out that the cross-coupling may lead to a decrease in the instantaneous current value when the inverter is turned on, thereby increasing the risk of losing the ZVS operating state. To eliminate the influence of cross-coupling, a parameter design method is proposed without additional devices and control. Finally, a 3-channel ISOP-IPT system prototype is built. The system achieves an energy transmission of 17.06 kW with an efficiency of 93.22%. Compared with single-channel systems, the power capacity is increased while keeping the input current level unchanged. After compensation, the system achieves equivalent decoupling in the case of cross-coupling, each channel works independently and maintains the input voltage balance.